siRNA silencing of FpVtg induces ovarian cell apoptosis in redtail prawn, Fenneropenaeus penicillatus - Kianann Tan1 ·; Yaxin Dong1 ·; Karsoon Tan; Lim, Leong‑Seng; Khor Waiho; Jing Chen; Peng Xu; Kwan, Kit Yue (Springer, 2023)
Inadequate gonadal maturation and poor spawning performance increasingly threaten the sustainability of shrimp aquaculture. Unraveling the mechanisms regulating ovarian development and maturation hence is critical to address industry challenges. Vitellogenin (Vtg), a precursor of yolk protein found in the hepatopancreas and ovary of shrimp, plays a key role in facilitating shrimp’s oocyte maturation and embryonic development after oviposition. This study found that FpVtg was specifically expressed in F. penicillatus hepatopancreas and ovary. FpVtg was localized predominantly in the oocyte cytoplasm and distributed uniformly in the hepatopancreas tissue. Silencing FpVtg led to apoptosis in both hepatopancreas and ovary tissues. Furthermore, FpVtg depletion upregulated the expression of ovarian peritrophin 1, ovarian peritrophin 2, serine proteinase inhibitor 6, and juvenile hormone esterase-like carboxylesterase 1, while downregulated that of vitellogenin, delta-9 desaturase, and insulin-like receptor. KEGG pathway analysis implicated such as PI3K-AKT signaling, RNA transport, ECM-receptor interaction, hippo signaling, oocyte meiosis, and apoptosis were enriched and involved in ovarian development. These findings have provided insights into the FpVtg’s reproductive role and the associated regulatory genes and pathways in F. penicillatus. This knowledge can contribute to establishing strategies to improve the breeding and aquaculture production of F. penicillatus by elucidating its vitellogenesis regulation in redtail prawn and other penaeid species. Further characterization of the implicated pathways and genes will clarify the intricacies underlying ovarian maturation.